HDAC6 regulates NF-κB signalling to control chondrocyte IL-1-induced MMP and inflammatory gene expression - Matt J. Barter; Andrew Butcher; Hui Wang; Dimitra Tsompani; Martin Galler; Ellen L. Rumsby; Kirsty L. Culley; Ian M. Clark; David A. Young (Scientific Reports, 2022)
Abstract Elevated pro-inflammatory signalling coupled with catabolic metalloproteinase expression is a common feature of arthritis, leading to cartilage damage, deterioration of the joint architecture and the associated pain and immobility. Countering these processes, histone deacetylase inhibitors (HDACi) have been shown to suppress matrix metalloproteinase (MMP) expression, block cytokine-induced signalling and reduce the cartilage degradation in animal models of the arthritis. In order to establish which specific HDACs account for these chondro-protective effects an HDAC1-11 RNAi screen was performed. HDAC6 was required for both the interleukin (IL)-1 induction of MMP expression and pro-inflammatory interleukin expression in chondrocytes, implicating an effect on NF-κB signalling. Depletion of HDAC6 post-transcriptionally up-regulated inhibitor of κB (IκB), prevented the nuclear translocation of NF-κB subunits and down-regulated NF-κB reporter activation. The pharmacological inhibition of HDAC6 reduced MMP expression in chondrocytes and cartilage collagen release. This work highlights the important role of HDAC6 in pro-inflammatory signalling and metalloproteinase gene expression, and identifies a part for HDAC6 in the NF-κB signalling pathway. By confirming the protection of cartilage this work supports the inhibition of HDAC6 as a possible therapeutic strategy in arthritis.